2020
DOI: 10.1080/10242694.2020.1791616
|View full text |Cite
|
Sign up to set email alerts
|

The Economic Costs of Hybrid Wars: The Case of Ukraine

Abstract: With more than ten thousand casualties, the ongoing hybrid Ukrainian war between pro-Russian separatists and the government in the Donbass region, Ukraine's productive core, has taken a severe toll on the country. Using cross-country panel data over the period 1995-2017, this paper estimates the causal effects of the Donbass war on Ukraine's GDP. Our counterfactual estimation by the synthetic control method shows that Ukraine's per capita GDP foregone due to the war amounts to 15.1% on average for 2013-2017. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 35 publications
1
7
0
1
Order By: Relevance
“…Before the outbreak of the war, relations between the two countries were not entirely peaceful, with several conflicts (in the form of a hybrid war) preceding the main military conflict in 2022. According to Bluszcz and Valente (2022), this ongoing hybrid war in the Donbass regiona region that represented the productive core of Ukraine-had a serious impact on the country's per capita GDP.…”
Section: The Russian -Ukrainian Warmentioning
confidence: 99%
“…Before the outbreak of the war, relations between the two countries were not entirely peaceful, with several conflicts (in the form of a hybrid war) preceding the main military conflict in 2022. According to Bluszcz and Valente (2022), this ongoing hybrid war in the Donbass regiona region that represented the productive core of Ukraine-had a serious impact on the country's per capita GDP.…”
Section: The Russian -Ukrainian Warmentioning
confidence: 99%
“…The authors argue that the effects of conflict have been short-term, with no statistical evidence of their long-term impact. Finally, Bluszcz and Valente [ 45 ] examined the causal impact of the Donbass war on the economy of Ukraine using cross-country data spanning from 1995–2017. The authors employed a synthetic control method and found that the per capita GDP of Ukraine that has foregone due to the war rounded to 15.1% during the period from 2013 to 2017, while during the period from 2013 to 2016, the war-effected regions, such as Donetsk and Luhansk, show a causal effect of 47%.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Now, remote temperature scanners are used extensively worldwide. • Major global events that occurred during the COVID- 19 pandemic-including the US-China trade war, 12 severe delays and congestion at ports and terminals due to COVID-19, 13 a global shortage of semiconductor chips, 14 inflation, 15 and the Ukraine-Russia war 16 -have influenced the application of smart technologies in healthcare. 17 • Existing methods based on AI are not easy to understand or communicate.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Chen and Wang 9 did not consider remote temperature scanners as the most suitable smart technology application, yet as COVID-19 remained prevalent in society, the cost-effectiveness of remote temperature scanners increased. Now, remote temperature scanners are used extensively worldwide. Major global events that occurred during the COVID-19 pandemic—including the US–China trade war, 12 severe delays and congestion at ports and terminals due to COVID-19, 13 a global shortage of semiconductor chips, 14 inflation, 15 and the Ukraine–Russia war 16 —have influenced the application of smart technologies in healthcare. 17 Existing methods based on AI are not easy to understand or communicate.…”
Section: Introductionmentioning
confidence: 99%